Choujin X. Volume 5 - Ishida, Sui (Viz signature., 2024)
"Tokio, Ely, and Azuma might be on a tropical island, but it's about as far from a vacation as you can get. They're there to undergo all kinds of intense training from the keepers of Yamato Mori to improve their choujin skills. Before they can make much headway, renegade choujin crash their training and try to kidnap one of the three for their mysterious boss! While their teachers bear the brunt of the attack, can Tokio and his friends protect themselves when they can't even control their powers yet?"--